Influencing adolescents' attitudes towards nicotine products: A systematic review - Vaihekoski Anu; Lagström Hanna; Eloranta Sini; Bäärs Susanna; Hannula Annika; Lehvikkö Mari; Salakari Minna (SAGE PUBLICATIONS LTD, 2022)
Background and aim: Use of nicotine can harm adolescents' brains and increase risk for future addiction to other drugs. Several international studies show that an acceptable attitude towards nicotine products increases the initiation or use of the products. Adolescents have limited or distorted knowledge about nicotine products. Many of them have a positive image of the properties and effects of nicotine products, which increases the chances of smoking or using snus. Yet, we know little about the relationship between youth nicotine use, youth attitudes towards nicotine products and the interventions to influence these attitudes. This systematic review synthesised adolescents' attitudes towards nicotine products and the ways to influence them. Methods: Systematic searches were carried out from PubMed, MEDLINE, CINAHL, and MEDIC databases and were targeted to randomised controlled trial (RCT) studies published in 2010-2021. Results: A total of seven RCT studies were reviewed with a total population (age range 9-17 years, adolescents 11-17 years) of 15,974. Findings were classified into four categories: school-based interventions, tobacco prevention campaigns, advertisements' influence on adolescents' opinions towards nicotine products, and their responses to cigarette pack warnings. Conclusion: Based on this systematic literature review, particularly school-based interventions have an effect on adolescents' attitudes towards smoking and preventing them from starting to smoke, when they are targeted before the age of puberty. School-based interventions should be further implemented and strengthened, as the school has been shown to have significant potential to support youth's health. There is a need for further information about the most effective interventions in the different age groups and the qualitative studies on the topic.